Banking evolution: navigating the realm of traditional and digital banking of Al Arafah Islami Bank PLC - Kabir, Humaiya (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, 2024.